Rhipicephalus sanguineus (Acari: Ixodidae) female ticks exposed to castor oil (Ricinus communis): An ultrastructural overview - Sampieri, B. R. [UNESP]; Furquim, K. C S [UNESP]; Nunes, P. H. [UNESP]; Camargo-Mathias, M. I. [UNESP] (Springer Nature, 2013)
Tick control has been accomplished through the use of synthetic acaricides, which has created resistant individuals, as well as contaminating the environment and nontarget organisms. Substances of plant origin, such as oils and extracts of eucalyptus and neem leaves, have been researched as an alternative to replace the synthetic acaricides. Ricinoleic acid esters from castor oil have recently been shown as a promising alternative in eliminating bacterial contamination during ethanol fermentation, by acting as an effective biocide. The same positive results have been observed when these esters are added to the food given to tick-infested rabbits. This study tested the effect of these substance on the reproductive system of Rhipicephalus sanguineus females, added to rabbit food, more specifically on oogenesis. For this, four groups were established: four control groups (CG1, CG2, CG3, and CG4) and four treatment groups (TG1, TG2, TG3, and TG4) with one rabbit in each (New Zealand White), used as hosts. After full 4 days feeding (semi-engorgement), the females were collected and had their ovaries extracted. In this study, it was observed that R. sanguineus females exposed to esters had their ovaries modified, which was demonstrated through transmission electron microscopy techniques. The addition of ricinoleic esters to the diet of tick-infested rabbits revealed how toxic such substances are for the cytoplasmic organelles of oocytes and pedicel cells. These compounds can change the morphophysiology of germ and somatic cells, consequently influencing their viability and, therefore, confirming that the ricinoleic acid esters from castor oil are a promising substance in the control of R. sanguineus. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: castor oil; ester; ricinoleic acid; animal experiment; animal tissue; cell organelle; cell ultrastructure; cell viability; controlled study; female; nonhuman; oocyte; oocyte development; ovary; priority journal; rabbit; Rhipicephalus sanguineus; Ricinus communis; somatic cell; transmission electron microscopy; Acaricides; Animals; Castor Oil; Diet; Female; Male; Microscopy, Electron, Transmission; Oogenesis; Ovary; Rabbits; Ricinoleic Acids; Acari; Azadirachta indica; Bacteria (microorganisms); Eucalyptus; Ixodida; Ixodidae; Oryctolagus cuniculus